2011
DOI: 10.1007/s10461-011-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Size, Composition, and Strength of Ties of Personal Social Support Networks Among Adult People Living with HIV/AIDS in Henan and Beijing, China

Abstract: To characterize the level of personal support available to people living with HIV/AIDS (PLWHA) in Henan and Beijing, China, face-to-face interviews were conducted to collect information on network size, composition, and strength of ties. The number of people as sources of support for participants in Henan varied from 1 to 13 and 1 to 16 in Beijing. In Henan, family members were more likely to provide support than non-relatives and they provided support more frequently; in Beijing non-relatives were more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Adams et al, 2002; Avogo and Agadjanian, 2008; Bignami-Van Assche, 2005; Edmonds et al, 2012; Fonseca-Becker and Valente, 2006; Green et al, 2011; Kohler et al, 2007; Miguel and Kremer, 2003; Moore, 2014; Moser and Mosler, 2008; Ruiz-Casares, 2010; Sandberg, 2012; White and Watkins, 2000; Wutich and McCarty, 2008; Zhang et al, 2012). Although these studies typically collect data about an actor's immediate contacts and the actor's perceptions of ties between those contacts, they cannot fully reveal structural aspects of the larger network in which actors are embedded nor explore the diffusion of behaviors, resources, technologies, and diseases through a larger set of people.…”
Section: Introductionmentioning
confidence: 99%
“…Adams et al, 2002; Avogo and Agadjanian, 2008; Bignami-Van Assche, 2005; Edmonds et al, 2012; Fonseca-Becker and Valente, 2006; Green et al, 2011; Kohler et al, 2007; Miguel and Kremer, 2003; Moore, 2014; Moser and Mosler, 2008; Ruiz-Casares, 2010; Sandberg, 2012; White and Watkins, 2000; Wutich and McCarty, 2008; Zhang et al, 2012). Although these studies typically collect data about an actor's immediate contacts and the actor's perceptions of ties between those contacts, they cannot fully reveal structural aspects of the larger network in which actors are embedded nor explore the diffusion of behaviors, resources, technologies, and diseases through a larger set of people.…”
Section: Introductionmentioning
confidence: 99%
“…40 As the evidence levels, 8 there was the following distribution: an article level II, 31 an article level IV 11 articles level VI. 1,[9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][37][38][39][40] It was found that most of the findings were derived from cross-sectional and descriptive studies, occurring direct observation of a planned number of people with HIV/ AIDS in a lifetime opportunity, which prevents comparisons of long-term sample characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…[52][53] In relation to perceived social support, family members were more involved in social support of people with HIV/ AIDS. 16,[36][37]39 In the context of HIV, the family emerges as a care unit, because they can contribute to the physical and mental balance of its members. The effects on physical, mental and emotional health caused by viruses extend to family members and those who are part of their social and personal relationships, as uncertainty about the contagion can generate fear, insecurity and emotional imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon receiving a diagnosis of HIV, for example, many older Finnish adults begin to actively establish new relationships with friends, especially with HIV support group members [19]. Several studies describe relatives and neighbors filling significant gaps in support networks, particularly after conflict or estrangement with former ties [20][21][22].…”
Section: Introductionmentioning
confidence: 99%